Risky sexual behaviors among orphaned youth in South Africa: findings of the 2017 population-based household survey - Noloyiso Vondo; Musawenkosi Mabaso; Vuyelwa Mehlomakulu; Ronel Sewpaul; Adlai Davids; Adlai Davids; Philisiwe Ndlovu; Derrick Sekgala; Londiwe Shandu; Sizulu Moyo; Sizulu Moyo (Frontiers Media S.A., 2023)
IntroductionIn sub-Saharan Africa, evidence shows that orphaned youth are exposed to more risky sexual behaviors than non-orphaned peers, which increases the chances of contracting HIV and other sexually transmitted infections. The fast rises in the prevalence of orphanhood are a result of the HIV/AIDS epidemic.MethodologyThe data for this secondary analysis were collected through a cross-sectional, multi-stage, stratified, cluster randomized sampling design. Multivariable backward stepwise logistic regression analysis was fitted to determine the factors associated with risky sexual behaviors among male and female adolescents and youth aged 12-24 years.ResultsOf 2,556 orphaned participants, 18.3% (95% CI: 14.3-23.0) had two or more sexual partners in the last 12 months, 31.3% (95% CI: 26.3-36.6) reported no condom use at last sex, and 98.3% (95% CI: 96.6-99.2) reported no consistent condom use. The likelihood of reporting multiple sexual partnerships was significantly lower among female adolescents, those residing in rural formal/farm areas, and those who reported sexual debut at age 15 years and was higher among those who reported sexual partners 5 years and older than their age group. The odds of not using a condom at last sex were significantly higher among female adolescents and those who perceived themselves as being at high risk of HIV infection and were significantly lower among those who had sexual debut at age 15 years and older.DiscussionThe findings suggest that there is a need for sexual risk-reduction strategies targeted at orphans, especially male orphans and those residing in urban areas. Such efforts should include behavior change interventions for delaying the age of sexual debut, changing HIV risk perception, mitigating multiple sexual partnerships, age-disparate sexual relationships, and enhancing condom use.